2016
DOI: 10.3201/eid2208.160043
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Fish and Frogs as Paratenic Hosts ofDracunculus medinensis, Chad

Abstract: Tadpoles fed infected copepods can harbor infective D. medinensis larvae and thus serve as potential paratenic hosts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
73
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 8 publications
0
73
0
Order By: Relevance
“…Tadpoles and frogs have long been known to experimentally support infective larvae of D. insignis ( 5 7 ), and just recently, they have been shown to experimentally support infective larvae of D. medinensis ( 2 ); however, natural infection with Dracunculus species has not previously been documented in any wild-caught amphibian. The finding of a wild-caught frog harboring a natural infection with a D. medinensis larva validates the findings of these experimental infections and demonstrates that such a paratenic host is likely involved in the transmission of D. medinensis larvae in Chad.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tadpoles and frogs have long been known to experimentally support infective larvae of D. insignis ( 5 7 ), and just recently, they have been shown to experimentally support infective larvae of D. medinensis ( 2 ); however, natural infection with Dracunculus species has not previously been documented in any wild-caught amphibian. The finding of a wild-caught frog harboring a natural infection with a D. medinensis larva validates the findings of these experimental infections and demonstrates that such a paratenic host is likely involved in the transmission of D. medinensis larvae in Chad.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the species identity of the frog, we extracted DNA from ethanol-fixed tissue and amplified the 16S ribosomal RNA gene ( 2 ). The sequence (450 bp) indicated that the frog was a ranid species in the genus Phrynobatrachus , most likely P. francisci because it shared 99% similarity with P. francisci sequences in GenBank (accession nos.…”
Section: The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work on Dracunculus and related spirurids indicates that paratenic hosts might be used to facilitate transmission ( 7 , 8 ). Recently, an experimental study showed D. medinensis worms could use tadpoles as paratenic hosts, and a naturally infected frog was detected in Chad ( 9 , 10 ).…”
mentioning
confidence: 99%
“…Experimental evidence has since shown that amphibians can also harbour viable D . medinensis larvae [10] but recently an infected frog has been found in Chad supporting the hypothesis that paratenic hosts contribute to Dracunculus epidemiology in that setting [11]. A suggested approach to control transmission was to educate the population as to how to dispose of fish entrails (to prevent dogs acquiring infection as they forage) and to ensure the fish were dried and cooked effectively to kill infective D .…”
mentioning
confidence: 99%